Manajemen Dakwah dalam Pembinaan Akhlak Remaja Masjid Ikhlasul Muhajirin Arcamanik Kota Bandung - Muhammad Muffty Pratama; Rodliyah Khuza'i; Hendi Suhendi (Bandung Conference Series: Islamic Broadcast Communication, 2024)
Abstract. This study is based on the large number of teenagers around the Ikhlasul Muhajirin Mosque, which does not guarantee that the teenagers are Muslims who obey Allah SWT, those who often consume alcohol, fight, speak rudely, have no manners towards their elders and other negative things. This study aims to determine the moral development program for teenagers at the Ikhlasul Muhajirin Arcamanik Mosque in Bandung City and to determine the results of the Ikhlasul Muhajirin Mosque Management in developing their morals. The object of the study was teenagers at the Ikhlasul Muhajirin Arcamanik Mosque in Bandung City. This study uses a qualitative approach with a descriptive method, the informant determination technique uses purposive sampling, data collection techniques, observation methods, interviews and documentation. The results of the study show that the moral development program for teenagers at the Ikhlasul Muhajirin Arcamanik Mosque in Bandung City is running well to develop adolescent moral behaviors such as behavior towards Allah SWT, humans and their environment. The morals of the Ikhlasul Muhajirin mosque youth are generally considered successful in terms of religious obedience, politeness and ethics, willingness to contribute and social concern as well as honor and respect for others are implemented according to the program carried out. And the management of the Ikhlasul Muhajirin mosque's da'wah was carried out quite well thanks to good cooperation and communication between the head of the Iklasul Muhajirin DKM as the mosque youth mentor and the youth of the Ikhlasul Muhajirin Arcamanik Mosque, Bandung City. Abstrak. Penelitian ini berlatar belakang dari banyaknya remaja sekitaran Masjid Ikhlasul Muhajirin tidak menjamin bahwa para remaja nya itu sebagai muslim yang taat kepada Allah SWT, mereka yang seringkali mengkonsumsi minuman keras, melakukan perkelahian, berkata kasar, tidak memiliki adab kepada yang lebih tua dan hal negative lainnya. Penelitian ini bertujuan untuk mengetahui program pembinaan akhlak remaja remaja Masjid Ikhlasul Muhajirin Arcamanik Kota Bandung serta untuk mengetahui hasil dari Manajemen Masjid Ikhlasul Muhajirin dalam pembinaan akhlaknya. Objek penelitiannya adalah remaja Masjid Ikhlasul Muhajirin Arcamanik Kota Bandung. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif, teknik penentuan informan menggunakan purposive sampling, teknik pengumpulan data, metode observasi, wawancara dan dokumentasi. Hasil penelitian menunjukan program pembinaan akhlak remaja Masjid Ikhlasul Muhajirin Arcamanik Kota Bandung berjalan dengan baik untuk mengembangkan perilaku-perilaku akhlak remaja seperti perilaku terhadap Allah SWT, manusia serta lingkungannya. Akhlak remaja Masjid Ikhlasul Muhajirin pada umumnya dinilai berhasil dari aspek ketaatan beragama, kesantunan dan etika, kesediaan berkontribusi dan kepedulian sosial serta kehormatan dan penghargaan terhadap orang lain terlaksana sesuai program yang dilakukan. Serta manajemen dakwah Masjid Ikhlasul Muhajirin terlaksana cukup baik berkat kerjasama dan komunikasi yang baik antara ketua DKM Iklasul Muhajirin selaku pembina remaja Masjid dengan remaja Masjid Ikhlasul Muhajirin Arcamanik Kota Bandung.